The physical world: Materialism or Idealism? A look from the sciences - Horvath, Jorge Ernesto (Cadernos de Astronomia, 2024)
We present in this article a discussion of the old problem of the nature of the physical world. The Idealist and Materialist positions are discussed and put in context in Classical Physics and the Quantum world, showing that the latter brings back old controversies within a new context. Can we ever establish to which extent the mind is responsible for the physical reality? These fundamental questions can serve as starting points for a discussion in the classroom with interesting interdisciplinary spinoffs.
Keywords: materialism; idealism; philosophy of science; quantum mechanics